End Point Estimate of Littlewood-Paley Operator Associated to the Generalized Schrödinger Operator. (20th March 2021) - Chen, Yanping; Tao, Wenyu
Abstract : Let L = − Δ + μ be the generalized Schrödinger operator on ℝ d, d ≥ 3, where μ ≠ 0 is a nonnegative Radon measure satisfying certain scale-invariant Kato conditions and doubling conditions. In this work, we give a new BMO space associated to the generalized Schrödinger operator L, BM O θ, L, which is bigger than the BMO spaces related to the classical Schrödinger operators A = − Δ + V, with V a potential satisfying a reverse Hölder inequality introduced by Dziubański et al. in 2005. Besides, the boundedness of the Littlewood-Paley operators associated to L in BM O θ, L also be proved.